Basin modelling of a complex rift system: The Northern Vøring Volcanic Margin case example. (25th November 2021) - Gac, Sébastien; Abdelmalak, Mansour M.; Faleide, Jan Inge; Schmid, Daniel W.; Zastrozhnov, Dmitry
Abstract: Extensional processes can lead to complex crustal configuration depending on the mechanisms of lithospheric thinning and the impact of magmatic additions during rifting and breakup. In this context, we studied the Vøring volcanic passive margin offshore Norway. The evolution of the inner Vøring Margin is well explained by standard models of lithosphere extension. However, these models fail to reproduce key observations at the outer (volcanic) province such as regional uplift at the time of breakup and excess magmatism. Therefore, additional processes are required to explain these observations. Excess magmatism and uplift have been related to mantle processes such as the arrival of the hot Icelandic mantle 'plume' or small‐scale convection processes. Melt retention in the asthenosphere has also been proposed to explain uplift. At last, mantle phase transitions during extension may contribute to uplift. We present tectonic and thermal models of basin evolution along a seismic profile crossing the Northern Vøring Margin. The thermal and isostatic history of basins is constrained through time‐forward basin modelling based on an automated inverse basin reconstruction approach. Two scenarios are evaluated: The first one includes pronounced mantle stretching during the last late Cretaceous‐Paleocene rifting event, and the second one includes late Paleocene‐early Eocene mantle thinning, at the breakup time around 56–54 Ma. Models incorporating late Paleocene‐early Eocene mantle thinning and taking into account magmatic processes (melt retention and magmatic underplate) and mantle phase transitions satisfactorily reproduce the specific observations of the outer (volcanic) margin. This result supports the contribution of the hot Iceland plume on the evolution of the Vøring Margin. Our results also indicate that thin‐crust models can produce a partially serpentinized mantle beneath the highly extended parts of the Vøring Basin. However, this model fails to reproduce observations. This suggests that serpentinization can occur locally but could not explain the entire lower crustal body nature. Abstract : A tectonic model incorporating late Paleocene‐early Eocene mantle thinning and taking into account magmatic processes (melt retention and magmatic underplate) and mantle phase transitions satisfactorily reproduce the specific observations of the outer (volcanic) margin such as uplift at the time of breakup and abundant magmatism. This result supports the contribution of the hot Iceland plume on the evolution of the Vøring Margin.